After the Berlin Wall Germany and Beyond - Gerstenberger, K.; Gerstenberger, K.; Braziel, J.; Braziel, J. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2011)
Twenty years after its fall, the wall that divided Berlin and Germany presents a conceptual paradox: on one hand, Germans have sought to erase it completely; on the other, it haunts the imagination in complex and often surprising ways.